PM2.5 source apportionment in the southeastern U.S.: Spatial and seasonal variations during 2001-2005 - YJ Chen; M* Zheng; Edgerton ES; Ke, L.; GY Sheng; JM Fu (J. Geophys. Res., 2012)
[1] The seasonal and spatial variations of source contributions of 112 composite fine particulate matter (PM2.5) samples collected in the Southeastern Aerosol Research and Characterization Study (SEARCH) monitoring network during 2001–2005 using molecular marker-based chemical mass balance (CMB-MM) model were determined. The lowest PM2.5 concentration occurs in January with higher values in warm months (maxima in July at four inland sites versus October at the coastal sites). Sulfate shows a similar pattern and plays a primary role in PM2.5 seasonality. Carbonaceous material (organic matter plus EC) exhibits less seasonality, but more spatial variations between the inland and coastal sites. Compared with the data at coastal sites, source attributions of diesel exhaust, gasoline exhaust, other organic matter (other OM), secondary sulfate, nitrate, and ammonium in PM2.5 mass at inland sites are higher. The difference in source attributions of wood combustion, meat cooking, vegetative detritus, and road dust among the eight sites is not significant. Contributions of eight primary sources to fine OC are wood burning (17 ± 19%), diesel exhaust (9 ± 4%), gasoline exhaust (5 ± 7%), meat cooking (5 ± 5%), road dust (2 ± 3%), vegetative detritus (2 ± 2%), cigarette smoke (2 ± 2% at four urban sites), and coke production (2 ± 1% only at BHM). Primary and secondary sources explain 82–100% of measured PM2.5 mass at the eight sites, including secondary ionic species (SO42−, NH4+, and NO3−; 41.4 ± 5.7%), identified OM (24.9 ± 11.3%), “other OM” (unexplained OM, 23.3 ± 10.3%), and “other mass” (11.4 ± 9.6%). Vehicle exhaust from both diesel and gasoline contributes the lowest fraction to PM2.5 mass in July and higher fractions at BHM and JST than other sites. Wood combustion, in contrast, contributes significantly to a larger fraction in winter than in summer. Road dust shows relatively high levels in July and April across the eight sites, while minor sources such as meat cooking and other sources (e.g., vegetative detritus, coke production, and cigarette smoke) show relatively small seasonal and spatial variations in the SEARCH monitoring network.